The Representation of Suicide on the Internet: Implications for Clinicians - Westerlund, Michael; Hadlaczky, Gergo; Wasserman, Danuta (JMIR Publications, 2012)
BackgroundSuicide is one of the major causes of death in the world, leading to approximately 1 million deaths per year. While much of what is said about suicide and its causes is still taboo in most contemporary societies and cultures, internet websites and discussion forums have become an important and controversial source of information on the subject. A great deal of ambivalence is discernible as to whether online communication about suicide primarily should be seen as an opportunity or a serious threat. ObjectiveTo investigate how the subject of suicide is represented on the Internet, based on hits generated by the search engine Google. MethodsIn an exploratory design, Google search results on the target word "suicide", for the years 2005, 2009, and 2012 respectively, were systematically analyzed and compared. ResultsThe study shows that web pages of institutional origin on the subject predominate, that the content provided by these institutions concerns primarily research and prevention, and that the form of communication used by these senders is almost exclusively monological. However, besides these institutional pages there are a substantial number of private senders and pages, often anti-medical and against treatment of depression and other mental problems, characterized by dialogue, confessions and narratives, and to a higher degree, an alternative pro-suicide stance. ConclusionsTo counteract the influence of anti-medical and pro-suicide information, the role of the Internet should be discussed with the patient in clinical practice. Dialogical and confessional communications provide an opportunity for the clinician to gain a deeper perspective into perceptions of patients, regarding both their afflictions and the role of medical treatment in their lives.